International Diplomacy and Colonial Retreat, ed. by Kent Fedorowich and Martin Thomas, Frank Cass Publishers, London 2001, ss. 260 / Adam Kosidło. - Kosidło, Adam (1947- ).
Recenzja książki: International Diplomacy and Colonial Retreat / editors Kent Fedorowich and Martin Thomas. - London ; Portland, 2001.